2017
DOI: 10.1183/13993003.01352-2017
|View full text |Cite
|
Sign up to set email alerts
|

Treating anxious expectations can improve dyspnoea in patients with COPD

Abstract: ]. Chronic obstructive pulmonary disease (COPD) is a worldwide leading cause of morbidity and mortality and associated with great individual, societal and economic burden [1]. Dyspnoea is the threatening cardinal symptom and related to a worse course of COPD, including drastic reductions in quality of life and even increased mortality risk [2, 3]. Dyspnoea is a multi-dimensional subjective experience that encompasses not only the perception of sensory signals (dyspnoea intensity), but also important immediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
6
12
0
Order By: Relevance
“…These findings converge with previous research on other neural gating modalities showing an association between reduced sensory gating and acute painful cold pressor stimulation [15]. Notably, higher anxiety was associated with stronger increases in dyspnoea reports, as well as stronger reductions in neural gating during increasing load levels, which confirms previous observations on either dyspnoea reports or neural gating alone [5][6][7].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…These findings converge with previous research on other neural gating modalities showing an association between reduced sensory gating and acute painful cold pressor stimulation [15]. Notably, higher anxiety was associated with stronger increases in dyspnoea reports, as well as stronger reductions in neural gating during increasing load levels, which confirms previous observations on either dyspnoea reports or neural gating alone [5][6][7].…”
supporting
confidence: 91%
“…This provides experimental support for the neural gating model of respiratory sensations and might partly be related to attentional processes [1,2]. Moreover, the findings support the view of a gating deficit as a potential mechanism for the common observation of over-perception of dyspnoea in more anxious individuals [1,2,5]. Subsequently, the present findings suggest a potential neural target for pharmacological and/or non-pharmacological treatments which necessitates further studies.…”
supporting
confidence: 81%
“…This necessitates future studies on vicarious dyspnoea in these caregivers. However, in a more positive vein, vicarious dyspnoea elicited by pictures, videos or even imaginary training [41] might be used in cognitive-behaviourally oriented interventions to desensitise those patients who (due to high levels of anticipatory fear of dyspnoea) avoid dyspnoea-related situations such as physical activities [42,43]. Similarly, vicarious dyspnoea might also be applied in the training of caregivers, who frequently underestimate dyspnoea in patients [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that the anticipation of imminent threat interferes with attentional allocation toward the source of threat and away from task-related errors as suggested by Moser et al (2005). Similarly, threat of dyspnea is a motivationally relevant stimulus that might claim attentional resources (Esser et al, 2017;Stoeckel, Esser, Gamer, Büchel, & von Leupoldt, 2016;von Leupoldt, 2017), which are not available for other cognitive processes (Hayen et al, 2013) in line with previous research on dual-task interference (Pashler, 1994). Notably, we found that threat of dyspnea reduced Pe mean amplitudes also for the correct response, but no effect was found for the Pe difference scores (error minus correct).…”
Section: Discussionmentioning
confidence: 99%
“…& Pané-Farré, 2017), anxious arousal even at rest (Pappens, Smets, Van den Bergh, & Van Diest, 2012), and the fearful avoidance of situations associated with dyspnea such as physical activity (von Leupoldt, 2017). Dyspnea causes a high socioeconomic and individual burden and is a strong predictor of morbidity and mortality in several patient groups (Banzett & O'Donnell, 2014;Bausewein et al, 2010;Lopez, 2006;Mannino & Buist, 2007;Mentz et al, 2015).…”
mentioning
confidence: 99%